Peran Orangtua dalam Mendidik Anak Sejak Usia Dini di Lingkungan Keluarga - Uswatul Hasni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Parents are the most instrumental in educating children from an early age. Parents have more time children than teachers. Parents must make themselves role models, educators and teachers for their children, teaches, assesses, evaluates and provides motivation for children to achieve what is expected for children because early childhood development depends on the environment and their families.